2006
DOI: 10.1002/pmic.200600299
|View full text |Cite
|
Sign up to set email alerts
|

A global proteomics approach identifies novel phosphorylated signaling proteins in GPVI‐activated platelets: Involvement of G6f, a novel platelet Grb2‐binding membrane adapter

Abstract: Collagen-related peptide (CRP) stimulates powerful activation of platelets through the GPVI-FcR γ-chain complex. We have combined proteomics and traditional biochemistry approaches to study the proteome of CRP-activated platelets, focusing in detail on tyrosine phosphorylation. In two separate approaches, phosphotyrosine immunoprecipitations followed by 1D-PAGE, and 2-DE, were used for protein separation. Proteins were identified by MS. By following these approaches, 96 proteins were found to undergo post-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 36 publications
5
75
0
Order By: Relevance
“…Previous studies have shown that platelet activation with the thrombin receptor-activating peptide or the GPVI agonist collagenrelated peptide induces diverse changes of the platelet proteome including phosphorylation events. 29,30 Thereby, novel signaling proteins (eg, adapter protein Dok-2 and type I transmembrane protein G6f) could be identified. 29,30 Some changes described were specific for GPVI, for example, tyrosine phosphorylation of G6f was found to occur in response to collagen but not in response to the G protein-coupled receptor agonists thrombin and ADP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that platelet activation with the thrombin receptor-activating peptide or the GPVI agonist collagenrelated peptide induces diverse changes of the platelet proteome including phosphorylation events. 29,30 Thereby, novel signaling proteins (eg, adapter protein Dok-2 and type I transmembrane protein G6f) could be identified. 29,30 Some changes described were specific for GPVI, for example, tyrosine phosphorylation of G6f was found to occur in response to collagen but not in response to the G protein-coupled receptor agonists thrombin and ADP.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, proteins from resting and collagen receptor-stimulated platelets were incubated with cAMP/cGMP-coupled beads, and the pull-down eluates were analyzed by LC-MS/MS. 115 Owing to the enrichment provided by specific probes, activity-based protein profiling 116-121 B, These studies are mainly (40%) based on 2-dimensional gel electrophoresis (2-DE)/ difference gel electrophoresis (DIGE), 46,52,53,80,82,83,85,87,88,90,91,[93][94][95][96]98,102,106,110,112,113 whereas gelfree methods (23%) are still under-represented. 21,42,89,97,[114][115][116][117][118]121 Combination refers to studies using 2-DE/DIGE in combination with other approaches.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
“…In contrast, state-of-the-art procedures use quantitative phosphoproteomics to monitor changes in phosphorylation levels of hundreds to thousands of peptides from relatively low sample amounts (≈0.1-1 mg of protein per condition), thus providing valuable insights into important biochemical processes. To date, mostly gel-based approaches in conjunction with phosphotyrosine immunoprecipitation have been used to study platelet signaling processes (eg, mediated by activation of thrombin receptors, 93,106,107,137 collagen receptors, 82,112 C-type lectin-like receptor 2, 138 and integrin α IIb β 3 outside-in signaling). 139 Because of the limitation in sensitivity, these approaches often did not provide MS-based identification of phosphorylation sites but identified new phosphoproteins and signaling pathways, hence expanding the knowledge about platelet regulation.…”
Section: Ptm and Signaling Proteomics In Plateletsmentioning
confidence: 99%
“…We have been among the pioneers in the field. 10,13,19,20 In this way, the complexity of outside-in and inside-out signaling has begun to be unraveled. However, redundancy in signaling pathways makes it difficult to identify clear therapeutic targets.…”
mentioning
confidence: 99%
“…Those inhibitors were used to make sure changes in the proteome were specifically due to GPVI signaling. 13 A comparison between basal (unactivated) and CRP-activated platelets was carried out for the 3 groups of patients (STEMI, SCAD, healthy). To do so, equal amounts of protein from each patient belonging to the same group were pooled for each study point (basal, CRP) and loaded in a 4% to 12% gradient Bis-Tris gel.…”
mentioning
confidence: 99%